An unprecedented 7-membered ring enamide cyclization through hypervalent iodine phenolic oxidation. Issue 23 (6th June 2018) - Berthiol, Florian; Philouze, Christian; Chavant, Pierre Y.; Poisson, Jean-François
Graphical abstract: Highlights: An original hypervalent iodine promoted 7-membered ring cyclization was discovered. An unusual and surprisingly stable hemi-aminal was isolated. A new approach in the total synthesis of galanthamine was investigated. Abstract: An unprecedented 7-membered ring cyclization of an enamide to a phenol through hypervalent iodine phenolic oxidation was discovered. In the process a molecule of solvent is incorporated on the cycle forming an unusual and stable hemi-aminal ether.